The impact of topical mupirocin on peritoneal dialysis infection rates in Singapore general hospital. - Lim, Christopher Thiam Seong; Wong, Kok Seng; Foo, Marjorie Wai Yin (Oxford University Press, 2005)
Background. Peritonitis and exit-site infections (ESI) are major causes of technique failure and morbidity in peritoneal dialysis (PD) patients. Topical mupirocin on the exit-site has been shown to reduce such complications and prolong life in PD. Since the year 2000, such an approach has been adopted for our new incident PD population. We now report the results of this new protocol. We also studied the effect of co-morbidity on peritonitis occurrence.